Studi Kasus Anak Usia 10 Bulan dengan Gizi Kurang di Desa Kuala Keureuto Barat Puskesmas Tanah Pasir Tahun 2025 - Mumtaz Alvira; Zahrawanda Ashfarina Muslim; Zikra Ihtasya Annabila; Muhammad Daniyal; Jarita Jarita; Noviana Zara (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Malnutrition is a condition in which the body does not receive enough essential nutrients, such as protein, vitamins, calories, and minerals, which causes various health problems, especially wasting and stunting, making it a serious concern in children. According to the Basic Health Research, the prevalence of malnourished children in Indonesia remained stable at 17.8% between 2016 and 2017 but decreased to 13.8% in 2018. This case study focuses on a 23-month-old girl from Kuala Keureuto Village, who was observed for three weeks through home visits in 2025. The diagnosis of malnutrition was made in accordance with national guidelines outlined in the Indonesian Minister of Health Regulation No. 2 of 2020, regarding child anthropometric standards. Anthropometric measurements showed that the child's height was 78.3 cm and her weight was 8.8 kg. Based on these measurements, her nutritional status was assessed as follows: A height/age Z-score between -2 and -3 SD indicates stunting, a weight/age Z-score between -2 and -3 SD indicates underweight, while a weight/age Z-score below -2 SD and a BMI/age Z-score below -2 SD are considered well-nourished. After confirming the diagnosis, the patient received nutrition education, supplemental feeding, appetite-stimulating supplements, and growth monitoring. In addition, analyses were conducted to identify factors influencing her condition, concluding that the malnutrition observed in this 23-month-old patient was influenced by parenting behavior, parental knowledge, medical history, incomplete immunizations, and environmental factors.